Digestibility of macronutrients and nitrogen balance in pregnant rabbits (Revista Española de Fisiología, 1987)
Primiparous New Zealand White does have been used to establish the weekly differences of several apparent digestibility coefficients (CDA) and the nitrogen balance, between pregnant and non-pregnant does, as well as the evolution of the same parameters along the state of gestation.The intake was 180 g/animal and day at the most.The results show that protein followed by dry matter CDAs were the most negatively affected in pregnant does with regard to the non-pregnant ones and throughout the gestation.For the other CDAs, the differences were only significant in the fourth week between pregnant and non-pregnant does, and also with regard to the remaining weeks of gestation.In this way, the organic matter and carbohydrate CDAs were lower whereas the fat one became higher.In relation to nitrogen balance, it was meaningfully greater in the third week of pregnancy with respect to the control animals.Also, a gradual increase may be observed throughout the gestation state, being especially important in the third and fourth week.